2013
DOI: 10.1073/pnas.1314829110
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional communication between oocytes and ovarian follicular somatic cells is required for meiotic arrest of mammalian oocytes

Abstract: Coordinated regulation of oocyte and ovarian follicular development is essential for fertility. In particular, the progression of meiosis, a germ cell-specific cell division that reduces the number of chromosomes from diploid to haploid, must be arrested until just before ovulation. Follicular somatic cells are well-known to impose this arrest, which is essential for oocyte-follicle developmental synchrony. Follicular somatic cells sustain meiotic arrest via the natriuretic peptide C/natriuretic peptide recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
134
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 173 publications
(143 citation statements)
references
References 57 publications
6
134
0
3
Order By: Relevance
“…Although the actual concentration of GDF9 in follicular fluid is unlikely to be as high as the dose (500 ng/ ml) that we have observed here to be effective in regulating Ddit4l expression and MTOR activation, genetic studies clearly show that both GDF9 and BMP15 are present in follicular fluid and function in synergy . Interestingly, GDF9 and BMP15 have recently been found to form a heterodimer that strongly stimulates cumulus cell functions in vitro (Mottershead et al, 2015;Peng et al, 2013;Wigglesworth et al, 2013). We also observed here that mouse recombinant GDF9-BMP15 heterodimer suppressed Ddit4l expression in oocytectomized cumulus cells even at 1 ng/ml, which was 500 times as potent as GDF9 homodimer.…”
Section: Contribution Of Oocytes To the Control Of The Differential Esupporting
confidence: 78%
“…Although the actual concentration of GDF9 in follicular fluid is unlikely to be as high as the dose (500 ng/ ml) that we have observed here to be effective in regulating Ddit4l expression and MTOR activation, genetic studies clearly show that both GDF9 and BMP15 are present in follicular fluid and function in synergy . Interestingly, GDF9 and BMP15 have recently been found to form a heterodimer that strongly stimulates cumulus cell functions in vitro (Mottershead et al, 2015;Peng et al, 2013;Wigglesworth et al, 2013). We also observed here that mouse recombinant GDF9-BMP15 heterodimer suppressed Ddit4l expression in oocytectomized cumulus cells even at 1 ng/ml, which was 500 times as potent as GDF9 homodimer.…”
Section: Contribution Of Oocytes To the Control Of The Differential Esupporting
confidence: 78%
“…3C, D). The function of the gap junctions that become assembled where the tips of the TZPs contact the oocyte plasma membrane has been extensively investigated and is well-understood (Phillips and Dekel, 1991;SelaAbramovich et al, 2006;Kidder and Vanderhyden, 2010;Wigglesworth et al, 2013;Winterhager and Kidder, 2015). Studies using radioactive tracers showed that sugars, amino acids and nucleotides were transferred from the granulosa cells to the oocyte (Eppig, 1979;Brower and Schultz, 1982).…”
Section: Function Of Tzpsmentioning
confidence: 99%
“…After coaxing mouse embryonic stem cells or induced pluripotent stem cells into a primordial germ cell-like state, the authors showed an age/stage-dependent requirement of the ovarian soma in order for the transplanted cells to become integrated into follicles capable of ovulating and producing oocytes with fertility potential, as shown by the birth of live young. These studies and others emphasize the critical nature of an ongoing dialogue between ovarian somatic cells that invokes a panoply of signaling mechanisms necessary to establish and maintain oocyte/follicle development to its ultimate state, ovulation (6,7). Indications from previous genetic manipulation studies identified key paracrine effectors at the interface between oocytes and somatic cells (8), but the extent to which these cues would be selfgenerating and operative in an in vitro culture system appeared to be problematic, given the enormous complexity at specific stages (6) and the many extrinsic factors now known to influence the dialogue in vivo (9).…”
Section: From a Backdrop To The Forefrontmentioning
confidence: 99%